Dual-gene detection in a single-tube system based on CRISPR-Cas12a/Cas13a for severe fever thrombocytopenia syndrome virus - Zhu, Yating; Xing, Chen; Yang, Li; Li, Qian; Wang, Xiaofeng; Zhou, Jing; Zhang, Cong; Ren, Cuiping; Liu, Fahu; He, Jun; Shen, Bing; Du, Yinan; et al. (Frontiers in Microbiology, 2022)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease, which is caused by severe fever with thrombocytopenia syndrome virus (SFTSV). The disease results in high mortality and increased morbidity, and raised a threat to global public health. Rapid detection of SFTSV is crucial for epidemic prevention in low-resource settings. Here we developed the deployable, sensitive and rapidly detection methods based on CRISPR/Cas12a or Cas13a technology. The detection assay based on CRISPR/Cas12a can stably detect the L gene or M gene of SFTSV at 10 cp/μl. And the method based on Cas13a can successfully detect the L gene of SFTSV as low as 0.75 cp/μl. For point-of-care testing (POCT), we combined fluorescence visualization and lateral flow detection with CRISPR/Cas-based detection assays. Furthermore, we present the dual-gene detection platform for SFTSV, which can simultaneously detect the L gene and M gene in one tube, using the orthogonal DNA/RNA collateral activity of the Cas12a/Cas13a system. On the basis of the dual-gene detection, we designed multiplexed test strips for the detection of SFTSV. All our methods were initially validated using 52 clinical samples, and the results exhibited 100% sensitivity and specificity. Overall, the new detection methods based on CRISPR/Cas can be promising candidates for on-site detection of SFTSV.